2018
DOI: 10.1515/text-2018-2017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ‘care leaver’ identity: A narrative analysis of personal experience stories

Abstract: People who spent time in public care as children are often represented as ‘care leavers’. This paper investigates how ‘care leaver’ is discursively constructed as a group identity, by analyzing 18 written personal experience stories from several charity websites by people identified or who self-identify as care leavers. Several approaches to narrative analysis are used: a clause-level analysis based on Labovʼs code scheme; the identification of turning points; an analysis of ‘identity work’; and an analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Viewed in this way, rather than contributing to an unhelpful discourse (Evans 2019), notions of turning points may serve to counter pervasive stereotypes of a homogenous, traumatized group of children and young people, destined for poor outcomes (Bakketeig et al 2020;Evans 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewed in this way, rather than contributing to an unhelpful discourse (Evans 2019), notions of turning points may serve to counter pervasive stereotypes of a homogenous, traumatized group of children and young people, destined for poor outcomes (Bakketeig et al 2020;Evans 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Offering an important critical consideration of turning points is Evans’ (2019) analysis of biographical writings produced by care leavers ( n = 18) for publication in charity reports or websites. Evans concluded that turning points were a recurrent feature of the stories, in which young people typically depicted positive change resultant from the intervention of others.…”
Section: Studies Of Turning Points In Relation To Out-of-home Care Ex...mentioning
confidence: 99%
“…In medical sociology, narrative approaches have been widely employed for understanding experiences of illness ( Thomas, 2010 ) and treatment ( Vindrola-Padros & Johnson, 2014 ), and how identities are constructed through narration of ongoing relationships between the “body, self and surrounding world” ( Hydén, 1997 , p. 51). Narratives have also proved valuable for exploring the representation of experiences and identities among marginalized groups such as care-leavers ( Evans, 2019 ). This reflects something of the origins of narratives in medical sociology, as a mode of giving voice to experiences that lie outside the dominant structures of biomedicine ( Hydén, 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, the researcher read closely the transcripts and reflections from each interview, to draw out and map by hand a chronological story for each participant, relating to PPI and their broader lives, structured loosely as “starting point,” “progression,” “current position,” and “future.” Second, the story was interpreted to elicit which personal identities were being presented and how, and the meaning attached to these through their narration. Third, the story was further interpreted to identify how the participant situated themselves and their experiences in relation to broader social and political stories, what Evans (2019) describes as “master narratives”: “cultural storylines” that constitute shared understanding between narrator and listener (p. 32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation